(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This paper deals withShakespeare’s portrayal of the common people as witty and intelligent humanbeings. Quite often, they outwit even kings and lords and expose their folliesand blunders in a subtle manner. Essentially, their wit is symbolic of thenotion and concept of age-old wisdom that goes with the common people andcombines tradition, pragmatism and culture. The common people are keenobservers of life in Shakespeare’s plays. They have not been to universitiesfor good education but they have practical wisdom about the worldly affairs.Their down-to-earth understanding of life and its complexity is based upontheir good and bad experiences. They seem to be completely immersed in thelocal culture in the play The MerryWives of Windsor (1599).